PERILAKU KEBERAGAMAAN DAN FENOMENA MEDIA SOSIAL TIK-TOK PADA GENERASI Z - Istika Ahdiyanti; Ida Waluyati (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2021)
Seeing from day to day digital growth is increasingly bombastic and it can't be avoided, one of the applications on social media, namely TikTok specifically has its own value in Generation Z which is the main subject in this study, researchers want to see how religious behavior and the phenomenon of TikTok in Generation Z is predicted to be a generation that is responsive to digital, but the presence of Tiktok is often a negative side for students, but basically there are always two sides, namely negative and positive for Generation Z students regarding their religious behavior. This research approach is qualitative with case study method, data collection techniques are; (1) Interview, the researcher interviewed 5 people who were considered related such as, parents of students (i) and related teachers (2) Observation by way of researchers observing directly in the field (3) documentation, in the form of pictures of research results, Data Analysis Techniques, namely reduction stage (simplification of data), display data (presentation of data) and verification of data (data conclusion). Research results From several interviews that have been conducted with several generation Z children, religious behavior and the TikTok phenomenon do not affect their religiosity if it can be taken from a positive perspective, but if you take a negative thing, it will also be negative for religious behavior. Negative behavior towards the diversity behavior of Generation Z is not solely because it is influenced by the TikTok application, because religious behavior is an outwardly wrong thing, TikTok users cannot use their time as well as possible because they are influenced by the TikTok application.